Effects of agricultural land tenure security on women’s labor participation in Ecuador - Pazos Navarro, Nicolas (2023)
The objective of this paper is to evaluate the effect of a rural land regularization program in Ecuador on women’s participation in the labour market. This program provided a georeferenced cadastral map to rural households, which is fundamental for land titling. Notably, when the treated land was inhabited by a couple, the program explicitly acknowledged joint ownership, thereby affirming the rights of both partners. The main hypothesis is that, for certain households, the program will enhance women’s land tenure security, thereby giving them a better outside option and increasing their bargaining power within the household. This may change intrahousehold work dynamics, as women might be inclined to allocate more of their time towards activities that provide them with private income. The study uses data collected for the program's impact evaluation, including both baseline and endline surveys. Using a combination of difference in difference and triple difference estimations, this study finds that providing women with land tenure security can affect the allocation of working time within the household, increasing women’s leisure time, increasing their participation in work within the household’s farm and shifting the household’s productive decisions to be more diverse and risk-averse. In general, the study shines a light on the impact of land tenure security on increased bargaining power.